Evaluate the following expression. 7^0

7^0 = 1 Anything to the power of zero equals 1.

Question

Asked 6/22/2011 10:35:03 AM

Updated 2/17/2014 6:53:26 PM

1 Answer/Comment

Rating

3

7^0 = 1

Anything to the power of zero equals 1.

Anything to the power of zero equals 1.

Added 2/17/2014 6:53:26 PM

This answer has been confirmed as correct and helpful.

Factor -x2y2 + x4 + 9y2 - 9x2

Question

Expert Answered

Updated 6/11/2014 12:39:37 AM

2 Answers/Comments

-x^2y^2 + x^4 + 9y^2 - 9x^2

= x^2(x^2 - y^2) - 9(x^2 - y^2)

= (x^2 - y^2)(x^2 - 9)

= (x + y)(x - y)(x + 3)(x - 3)

= x^2(x^2 - y^2) - 9(x^2 - y^2)

= (x^2 - y^2)(x^2 - 9)

= (x + y)(x - y)(x + 3)(x - 3)

Added 6/11/2014 12:38:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/11/2014 12:55:28 AM]

(5x2 + 2x - 3)(x - 1) answer choices are: A. 5x - 2x2 + 3x4
B. 5x2 - 5x - 1
C. 7x3 + 6x2 - 1x
D.5x3 - 3x2 - 5x + 3 **Weegy:** D. Please rate the answer. (More)

Question

Expert Answered

Updated 314 days ago|1/9/2018 4:58:38 AM

1 Answer/Comment

(5x^2 + 2x - 3)(x - 1)

= 5x^3 + 2x^2 - 3x - 5x^2 - 2x + 3

= 5x^3 - 3x^2 - 5x + 3

= 5x^3 + 2x^2 - 3x - 5x^2 - 2x + 3

= 5x^3 - 3x^2 - 5x + 3

Added 314 days ago|1/9/2018 4:58:38 AM

This answer has been confirmed as correct and helpful.

(5x2 + 2x - 3)(x - 1)

Question

Not Answered

Updated 3/8/2014 4:57:34 AM

1 Answer/Comment

(5x2 + 2x - 3)(x - 1)

= 5x^3 - 3x^2 - 5x + 3

= 5x^3 - 3x^2 - 5x + 3

Added 3/8/2014 4:57:32 AM

This answer has been confirmed as correct and helpful.

27,694,301

questions answered

There are no comments.